Effect Effect Of Product Innovation, Networking, And Marketing Innovation on E-Commerce - Yonatan, Nicky Liane; Hapzi Ali; Yayan Hendayana (Dinasti International Journal of Management Science, 2024)
The effect of Product Innovation, networking and Marketing Innovation on E-Commerce is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Product Innovation has an effect on E-Commerce; 2) Networking has an effect on E-Commerce; and 3) Marketing Innovation has an effect on E-Commerce.